Amy Noble: capstone - Noble, Amy, artist (Colorado State University. Libraries, 2021)
The artist's statement: I am a firm believer that there is a difference between being an artist, and being a designer. Simply put, an artist creates for themselves, while a designer creates for other people. The differences between the two however, in my mind, are interchangeable and just because someone is a designer, doesn't mean they aren't an artist. I consider myself an artist, a designer, and a journalist. While the work I create for myself lies closely to the work of a true artist, journalistic design is where my strengths are grounded. On the other hand, as a design intern at the branding experience company, Monigle, I am able to develop my skills in branding and identity creation, a realm that is more typically considered when thinking of graphic design. My true interest lies in the visual identity of printed publications. Great journalism has the power to make each reader's life richer and more fulfilling, and I believe that it can be greater with exceptional design. The opportunity for my work to reach others on a public platform for the purpose of good, impactful, and truthful journalism is an indescribable desire I have, and while I am not there yet, I will be there soon. While I am often inspired by the work of others, drawing from the best to create even greater works of art and design, my cultural identity is where I draw a lot of inspiration from. I identify as what is known as a "Third Culture Kid" - I am an American citizen, born in Australia and raised in England. This is a huge part of who I am, and because of my cultural experiences, I have a broader understanding of the world around me, from which I often find myself referring back to when coming up with new concepts and ideas. I am genuinely inspired by the world of art and design and with everything I create, I do so with determination, purpose and true passion.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design